Climate change dynamics for global energy security and equity: Evidence from policy stringency drivers - Dagar, Vishal (2024)
This study investigates the dynamic interplay between financial integration, political stability, infrastructure, and global integration in enhancing Energy Security (ES) and Energy Equity (EE) across 50 economies from 2006 to 2018. It addresses gaps in understanding how socio-economic, political, and technological factors collectively influence ES and EE during the global transition from fossil fuels to renewable energy sources. The research aims to reveal the complex relationships and potential trade-offs between energy sustainability, economic growth, and equitable energy distribution. Utilizing robust panel data methods including System GMM, Fixed Effects, and Random Effects, the study examines the impacts of various determinants on ES and EE. The dataset includes annual observations on global integration, financial integration, infrastructure quality, political stability, and other relevant metrics from diverse global sources. The findings reveal that increased financial integration significantly enhances ES by easing capital flow into energy infrastructure, which is crucial for stable energy supply chains. Political stability also positively affects ES, underscoring the importance of stable governance in sustaining energy policies. Conversely, rapid urban growth and inadequate social integration pose challenges to achieving EE, highlighting disparities in energy access worsened by urbanization. Technological advancements and digital connectivity appear as positive drivers for EE, enhancing the efficiency and distribution of energy resources. This study contributes to the literature by providing a detailed examination of how integration into global financial and political systems affects energy strategies at a national level. It offers valuable insights for policymakers on fostering environments conducive to sustainable energy development and fair energy access. The research underscores the importance of incorporating socio-economic and technological advancements in energy policy frameworks to achieve balanced growth and sustainability. Future research directions include exploring the causal relationships and long-term impacts of these factors on ES and EE, particularly in the context of evolving global energy policies and technological advancements.